2012
DOI: 10.1007/s00223-011-9567-0
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Analysis of the Long Bone Abnormality (lbab/lbab) Mouse, A Novel Chondrodysplastic C-Type Natriuretic Peptide Mutant

Abstract: Long bone abnormality (lbab/lbab) is a strain of dwarf mice. Recent studies revealed that the phenotype is caused by a spontaneous mutation in the Nppc gene, which encodes mouse C-type natriuretic peptide (CNP). In this study, we analyzed the chondrodysplastic skeletal phenotype of lbab/lbab mice. At birth, lbab/lbab mice are only slightly shorter than their wild-type littermates. Nevertheless, lbab/lbab mice do not undergo a growth spurt, and their final body and bone lengths are only ~60% of those of wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Similarly, the “long bone abnormality” ( lbab / lbab ) mice, mutants due to a spontaneous autosomal recessive hypomorphic mutation in the Nppc gene, developed severe dwarfism characterized by short tails and extremities, while heterozygous mice did not differ from wild-type mice. These studies confirmed that haploinsufficiency of the NPPC gene does not exist in mice [17]. On the contrary, the effects of haploinsufficiency of this gene are evident in humans which could be due to differences between species or some other unknown mechanism(s).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, the “long bone abnormality” ( lbab / lbab ) mice, mutants due to a spontaneous autosomal recessive hypomorphic mutation in the Nppc gene, developed severe dwarfism characterized by short tails and extremities, while heterozygous mice did not differ from wild-type mice. These studies confirmed that haploinsufficiency of the NPPC gene does not exist in mice [17]. On the contrary, the effects of haploinsufficiency of this gene are evident in humans which could be due to differences between species or some other unknown mechanism(s).…”
Section: Discussionsupporting
confidence: 59%
“…On the contrary, the effects of haploinsufficiency of this gene are evident in humans which could be due to differences between species or some other unknown mechanism(s). CNP is especially crucial for skeletal growth spurt that occurs in early life, is expressed in the growth plate cartilage, and works as an autocrine/paracrine regulator [17]. In the study by Moncla et al [12], the NPPC gene was not expressed in normal lymphoblasts under normal conditions while it is expressed 6-fold in chondrocytes of his patient P1.…”
Section: Discussionmentioning
confidence: 93%
“…173,174 Another study has shown that inhibition of CNP synthesis reduces both bone volume and trabecular thickness in the humerus of mice, and these values are further restored when these mice are crossed with animals overexpressing CNP in cartilage tissue. 175 CNP also increased collagen synthesis and enhanced chondrocytes proliferation and differentiation in an autocrine/ paracrine manner. 176,177 CNP may represent a valuable avenue to enhance bone growth, however its action on cardiac and vascular functions raise concerns on its use.…”
Section: A C-type Natriuretic Peptide (Cnp)mentioning
confidence: 92%
“…Mice with systemic depletion of CNP are dwarf, whereas overproduction of CNP in cartilage resulted in prominent skeletal overgrowth and deformations . Another study has shown that inhibition of CNP synthesis reduces both bone volume and trabecular thickness in the humerus of mice, and these values are further restored when these mice are crossed with animals overexpressing CNP in cartilage tissue . CNP also increased collagen synthesis and enhanced chondrocytes proliferation and differentiation in an autocrine/paracrine manner …”
Section: Peptides From the Vascular Systemmentioning
confidence: 99%
“…Since profoundly reduced postnatal growth in mice with homozygous mutations in NPPC (long bone abnormal, lbab) is rescued by CNP agonists [66], early detection of this putative genetic disorder in humans will be important, as the condition is likely to be uniquely responsive to exogenous CNP. Dominant activating mutations of FGFR3 , such as those causing achondroplasia, result in profoundly disproportional short stature and are associated with inappropriately raised plasma concentrations of both CNP and NTproCNP [50] in both children and adults.…”
Section: Plasma Cnp Products and Genetic Disorders Of Growthmentioning
confidence: 99%